2017
DOI: 10.1590/1516-3180.2016.0224141116
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of outpatient expenditure within primary care in the Brazilian National Health System

Abstract: CONTEXT AND OBJECTIVE: One of the big challenges facing governments worldwide is the financing of healthcare systems. Thus, it is necessary to understand the factors and key components associated with healthcare expenditure. The aim here was to identify demographic, socioeconomic, lifestyle and clinical factors associated with direct healthcare expenditure within primary care, among adults attended through the Brazilian National Health System in the city of Bauru. DESIGN AND SETTING: Cross-sectional study cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
14
0
3
Order By: Relevance
“…También se encontró que la procedencia urbana, tener mayor nivel de educación, padecer una enfermedad crónica, así como, tener mayores gastos per cápita aumentan las posibilidades y los niveles de GBS. Estos hallazgos son consistentes con los resultados de Bock et al (6) , Gong et al (7) , Turi et al (10) y Corrieri et al (13) . La fuerte asociación reportada entre el nivel de GBS y los quintiles de gasto per cápita sugiere que la proporción GBS/gasto per cápita es desfavorable para los socialmente desaventajados, como Proaño y Bernabé lo señalan en su estudio (26) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…También se encontró que la procedencia urbana, tener mayor nivel de educación, padecer una enfermedad crónica, así como, tener mayores gastos per cápita aumentan las posibilidades y los niveles de GBS. Estos hallazgos son consistentes con los resultados de Bock et al (6) , Gong et al (7) , Turi et al (10) y Corrieri et al (13) . La fuerte asociación reportada entre el nivel de GBS y los quintiles de gasto per cápita sugiere que la proporción GBS/gasto per cápita es desfavorable para los socialmente desaventajados, como Proaño y Bernabé lo señalan en su estudio (26) .…”
Section: Discussionunclassified
“…Se han encontrado diversos factores que se asocian al GBS, como por ejemplo, sexo, edad, área de residencia, nivel de educación, ingresos, presencia de enfermedades crónicas y disponer de un seguro de salud (5)(6)(7)(8)(9)(10)(11)(12) . Así, los adultos mayores con bajos ingresos tienen una mayor proporción de GBS en relación con sus ingresos, un menor nivel educativo se asocia con un mayor GBS, la falta de cobertura de un seguro de salud y el sexo femenino presentan GBS más alto debido a sus menores ingresos y menor tasa de participación laboral (13) .…”
Section: Mensajes Clave Introducciónunclassified
“…Increases in Body Mass Index (BMI) that characterize overweight and obesity are associated with higher need for and expenditures with medications, primarily for the treatment of hypertension, diabetes and cardiovascular disease. [1][2][3][4][5][6][7][8][9] Considering the rising costs of health care and the escalating burden of obesity in diverse countries, there has been increasing trends in examination of cost-effectiveness of health interventions towards prevention and treatment of obesity and its effects on comorbidities. [10][11][12][13][14][15] Recent evidence on the impacts of obesity-related interventions, including prevention [16][17][18] (promotion of physical activity and healthy eating) and treatment (medication and/or surgical procedures) strategies [19][20][21][22][23][24] , have demonstrated that efficacy of bariatric surgery with multi-disciplinary approach decreasing body weight and improving of health including cancer, cardiovascular events, T2DM, dyslipidemia, life expectancy, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,5,6,7,8,9,10,11,12,13), X t =0 for time points in stage 1 (time points 1, 2, 3, 4, 5 and 6) and 1 for time points in stage 2 (time points 7, 8, 9, 10, 11, 12 and 13), and (XT) t =0 for time points instage 1, and (t−4) for time points in stage 2. The regression coefficient for T t represents the rate of change of activity in stage 1, and the sum of regression coefficients for T t and (XT) t is the rate of change of activity in stage 2.…”
mentioning
confidence: 99%
“…Frente ao que foi exposto sobre o SUS e o contexto brasileiro, a distribuição de recursos de saúde é insuficiente e por consequência direta tem-se a não garantia de acesso de todos ao sistema único de saúde, e este financiamento é um dos maiores desafios para efetivação do SUS, principalmente nos países em desenvolvimento, como o Brasil, devido a orçamentos limitados e, também, ao aumento da prevalência de doenças crônicas (TURI et al, 2017). Para além do baixo financiamento, é visto a depredação ao longo do tempo de pouco investimento daquilo que já existe: hospitais e unidades de saúde mal conservadas, sucateadas e com má gestão.…”
Section: Cenário De Saúde No Brasil E Doenças Oncológicasunclassified